2013
DOI: 10.1177/0969141313514217
|View full text |Cite
|
Sign up to set email alerts
|

Newborn bloodspot results: predictive value of screen positive test for thalassaemia major

Abstract: Aim: There are limited published data on the performance of the percentage of haemoglobin A (Hb A) as a screening test for beta thalassaemia major in the newborn period. This paper aims to analyse data derived from a national newborn bloodspot screening programme for sickle cell disease on the performance of haemoglobin A (Hb A) as a screening test for beta thalassaemia major in the newborn period. Methods: Newborn bloodspot sickle cell screening data from 2,288,008 babies were analysed. Data reported to the N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 3 publications
(8 reference statements)
2
10
1
Order By: Relevance
“…The putative identification of newborns affected with SCD is simple and very sensitive with the methods used. 16 14,15,19 In our study, all SCD-positive screening tests were confirmed, except for two patients not retrieved despite much effort. We did not observe, however, a high false-positive result even in the few cases of extremely preterm newborns, as described elsewhere.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The putative identification of newborns affected with SCD is simple and very sensitive with the methods used. 16 14,15,19 In our study, all SCD-positive screening tests were confirmed, except for two patients not retrieved despite much effort. We did not observe, however, a high false-positive result even in the few cases of extremely preterm newborns, as described elsewhere.…”
Section: Discussionsupporting
confidence: 62%
“…Our chosen screening cutoff related to the low HbA value is currently under prospective validation (study in progress). With the expression of Hb percentages in MoM, a single threshold independent of term of pregnancy could potentially be used, in contrast to other studies where different thresholds have been chosen based on the distribution of HbA% in normal full‐term neonates …”
Section: Discussionmentioning
confidence: 99%
“…Several of the deaths were in affected babies who were born prematurely, had interuterine growth retardation or other complications as noted elsewhere. 30 31 …”
Section: Discussionmentioning
confidence: 99%
“…Beta thalassemia continues to be reported when found in NBS for SCD, and this has been due to lack of available evidence on the efficacy of detection and the clinical justification for early detection. There is now improved evidence on the sensitivity and specificity of the test [9,10]. However published clinical evidence remains scarce.…”
Section: Discussionmentioning
confidence: 99%